REGISTER RESEP MASAKAN DALAM TABLOID SAJI : KAJIAN SOSIOLINGUISTIK - Syafitri Rizki Pratiwi; Nusarini Nusarini (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to (1) Describe the form of registers in recipes in Saji tabloid, (2) Describe the meaning of registers in recipes in Saji tabloid, (3) Describe the function of register languages in recipes in Saji tabloids. This type of research is qualitative research. The data used is in the form of sentences in written language in which there are typical words or phrases. The data source in this study uses the Saji tabloid print media. Data were obtained by using the refer method with proficient non-engaging and note-taking techniques. Data were analyzed by referential equivalent methods. Besides that, this study also uses the secondary method of advanced techniques, namely sloping techniques and insertion techniques. The method of presenting the results of data analysis uses an informal data presentation model. The results of this study are as follows. (1) Form registers in recipes in Saji tabloid are (a) single word register, (b) complex form registers, including affixed words, reduplication, and abbreviation, (c) phrase form registers including exocentric phrases and endocentric phrases consisting for two words. (2) The meaning of the register in the recipe in the Saji tabloid includes (a) lexical meaning and (b) grammatical meaning. (3) The function of the registered language in the recipe in the Saji tabloid is a referential function.